Accelerating regional cooperation and integration in Asia and the Pacific 2017 conference highlights. (Asian Development Bank, 2019)
RCI is vital for Asia and the Pacific development. It plays a critical role in accelerating economic growth, reducing poverty and economic disparity, raising productivity and employment, and strengthening institutions. For the Asian Development Bank, fostering RCI is a cornerstone of its support to its developing member countries and helps amplify the impact of its other investments. The report focuses on economic corridors, emerging RCI initiatives, cooperation for financial stability and resilience, and regional public goods.